The literary re-placement of ‘Iran’ in India: The Qeṣṣe-ye Sanjān of the Zoroastrian ‘Persians’ (Parsis) - Williams, Alan (Acta Orientalia Vilnensia, 2007)
University of Manchester The Persian Qeṣṣe-ye Sanjān (‘the Story of Sanjān’), written in 1599 CE, is our only source for the account of the supposed Zoroastrian ‘migration’ from Iran to India in the 8th cent. The last of the Sasanian kings, Yazdegard III, had been deposed after the battle of Nehāvand in 642 CE, and Zoroastrian Iran was overrun by Arab invaders who Islamicized Iran after hundreds of years of Zoroastrian domination of the country under Achaemenian, Parthian and Sasanian empires (530 BCE–651 CE). According to the Qeṣṣe-ye Sanjān, ‘Iran’ was ‘shattered’ by the Arab conquest, and those who remained faithful to the old religion fled from persecution by the new Muslim presence. The Qeṣṣe-ye Sanjān tells of the long journey of a group of Zoroastrians to seek asylum in India, and the subsequent resettlement there, where they later became the Parsis, ‘the Persians’. The key factor in this re-placement of Iran is their finding a new monarch, not in human form but in a sacred fire, called ‘King of Iran’. When it is read as a myth of charter and series of rites de passage, it reveals much about the literary construction of place as a form of religious and social commentary.